A )√18 + √8 - √50 + √32 =
b )2√3 +√12 - √48 + √75 =
c )√20 + √45 + √90 - 2√125 =
d )√24 + √54 - √96 - √150 =
e )2√18 + 3√8 +3√32 - √50 =
f )2√20 - √45 +3√18 +√72 - √80 =
g )0.5√24 - 3√40 - (√150 - √1000) =

Zapisz w najprostszej postaci

2

Odpowiedzi

2009-11-19T19:17:20+01:00
2009-11-19T19:55:42+01:00
A )√18 + √8 - √50 + √32 =√9*2+√4*2-√25*2+√16*2=3√2+2√2-5√2+4√2=4√2

b )2√3 +√12 - √48 + √75 =2√3+√4*3-√16*3+√25*3=2√3+2√3-4√3+5√3=5√3

c )√20 + √45 + √90 - 2√125=
=√4*5+√9*5+√9*2*5-2√25*5=2√5+3√5+3√2*√5-2*5√5=
=5√5+3√2*√5-10√5=3√2*√5-5√5=√5*(3√2-5)

d )√24 + √54 - √96 - √150 =
=√4*6+√9*6-√16*6-√25*6=2√6+3√6-4√6-5√6=-4√6

e )2√18 + 3√8 +3√32 - √50 =2√9*2+3√4*2+3√16*2-√25*2=
=2*3√2+3*2√2+3*4√2-5√2=6√2+6√2+12√2-5√2=19√2

f )2√20 - √45 +3√18 +√72 - √80 =2*√4*5-√9*5+3*√9*2+√36*2=
=2*2√5-3√5+3*3√2+6√2=4√5-3√5+9√2+6√2=√5+15√2

g )0.5√24 - 3√40 - (√150 - √1000) =0,5√4*6-3√4*10-√25*6+√100*10=
=0,5*2√6-3*2√10-5√6+10√10=-4√6+4√10=4(√10-√6)